Genome-wide analysis in Plasmodium falciparum reveals early and late phases of RNA polymerase II occupancy during the infectious cycle - Rai, Ragini (2015)
Background: Over the course of its intraerythrocytic developmental cycle (IDC), the malaria parasite Plasmodium falciparum tightly orchestrates the rise and fall of transcript levels for hundreds of genes. Considerable debate has focused on the relative importance of transcriptional versus post-transcriptional processes in the regulation of transcript levels. Enzymatically active forms of RNAPII in other organisms have been associated with phosphorylation on the serines at positions 2 and 5 of the heptad repeats within the C-terminal domain (CTD) of RNAPII. We reasoned that insight into the contribution of transcriptional mechanisms to gene expression in P. falciparum could be obtained by comparing the presence of enzymatically active forms of RNAPII at multiple genes with the abundance of their associated transcripts.